DOI: 10.22616/lludissert/2014.003
|View full text |Cite
|
Sign up to set email alerts
|

Baltijas jūras piekrastes ainavu identitāte Latvijā = The Baltic Sea Coastal Landscape Identity in Latvia

Abstract: sociālie un politiskie notikumi, kas tieši ietekmē nacionālo identitāti un atspoguļojas ainavas identitātē [94,306,168,155,234,197,154]. Katram ainavas mērogam ainavas identitāte definējama atsevišķi, jo katru uztveres un plānošanas mērogu iezīmē atšķirīgas elementu grupas un ir dažāds elementu skaits. Tas palielinās, virzoties no liela mēroga līdz mazām, lokālam mērogam [93,114,46,187,227,154]. Ainavas identitātes pētījumi visbiežāk atspoguļo lokālo ainavas mērogu, pievēršoties konkrētas vietas aurai, kultūrv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
0
0
Order By: Relevance
“…In such a process and under the pressure of globalisation, the mental symbols of landscape or place turn into a commodity typical of the age of capitalism [16,33,35]. The concept of landscape identity itself encompasses many of the symbolic meanings and expressions of the landscape, so it can be concluded that the symbolic meaning of the landscape is a part of the concept of landscape identity, where cognitive aspects play an equally important role as cultural-historical and physical aspects of the landscape [ 26,28].…”
Section: The Paintings By ģ Eliass [From Author Private Archive] Land...mentioning
confidence: 99%
“…In such a process and under the pressure of globalisation, the mental symbols of landscape or place turn into a commodity typical of the age of capitalism [16,33,35]. The concept of landscape identity itself encompasses many of the symbolic meanings and expressions of the landscape, so it can be concluded that the symbolic meaning of the landscape is a part of the concept of landscape identity, where cognitive aspects play an equally important role as cultural-historical and physical aspects of the landscape [ 26,28].…”
Section: The Paintings By ģ Eliass [From Author Private Archive] Land...mentioning
confidence: 99%